2017
DOI: 10.1136/bjsports-2016-097270.12
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking a biomarker for concussion in the paediatricpediatric population

Abstract: Objective The study aims to validate eye movement tracking performed without a baseline study as a biomarker for concussion in a paediatric population.DesignThis is a cross-sectional case control study of patients diagnosed with concussion in a referral centre compared to non-concussed controls.MethodsEye movements were recorded with an SR Research Eyelink 1000 eye tracker while a 220-second video was played. Eye tracking metrics were compared to Acute Concussion Evaluation (ACE) scores and clinical assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, in sports concussion studies it is common to consider the movement of both eyes as conjugate. The two exceptions in the current review are the line of research pursued by Samadani et al (2017) who previously investigated the movement of the right and left eyes separately and found that the concussed population was less capable of generating coordinated eye movement , and the study by Danna-dos-Santos et al (2018) who measured both eyes separately and found no asymmetries between right and left eyes.…”
Section: Measures Of Latency and Distancementioning
confidence: 66%
“…However, in sports concussion studies it is common to consider the movement of both eyes as conjugate. The two exceptions in the current review are the line of research pursued by Samadani et al (2017) who previously investigated the movement of the right and left eyes separately and found that the concussed population was less capable of generating coordinated eye movement , and the study by Danna-dos-Santos et al (2018) who measured both eyes separately and found no asymmetries between right and left eyes.…”
Section: Measures Of Latency and Distancementioning
confidence: 66%
“…9,10 We selected 17 variables to analyze within this investigation based on prior work that has used this experimental setup to define eye movement velocity, movement distance, or trajectory areas. 5,9 Many of these variables possess moderate levels of reliability among uninjured adolescent athletes, 16 and evaluate the distance the eye traverses during the trial, the variability of movement of each eye, and the ratio of the movement and variability of the 2 eyes moving together. The total distance covered refers to the amount of measured eye movement in each plane along each side (top, bottom, left, and right) of the computer monitor.…”
Section: Eye Tracking Assessmentmentioning
confidence: 99%
“…Visual disturbances have been documented in recent investigations among the adolescent population with concussion. [4][5][6][7][8] Thus, quantifying the effect of concussion on vision in adolescents may help to specify areas of dysfunction.…”
mentioning
confidence: 99%
“…Eye tracking enables objective, quantifiable, dense, and repeatable measurement of oculomotor indices as the overt expression of neurobiological substates driving attentional processes (Posner & Petersen, 1990). There is a growing body of work examining the potential of eye tracking as a biomarker in conditions ranging from traumatic brain injury (Bin Zahid et al, 2020; Hunfalvay et al, 2021; Samadani et al, 2016, 2017; for review see McDonald et al, 2022), to Parkinson's disease (Ba et al, 2022; Blekher et al, 2009; Brien et al, 2023; Li et al, 2023; Tsitsi et al, 2021), to autism (Bradshaw et al, 2019; Del Valle Rubido et al, 2020; Frazier et al, 2021; Loth et al, 2017; Mason et al, 2021; Murias et al, 2018; Pierce et al, 2015; Shic et al, 2022; Wen et al, 2022), though discussions regarding nomenclature are ongoing, as they are for other similar classes of biomarkers (Ba et al, 2022; Hidalgo‐Mazzei et al, 2018; Li et al, 2023; Tsitsi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%